2013
DOI: 10.1017/s0021932013000527
|View full text |Cite
|
Sign up to set email alerts
|

Lessons From History of Socioeconomic Improvements: A New Approach to Treating Multi-Drug-Resistant Tuberculosis

Abstract: Summary This study investigated the trends in tuberculosis mortality through time in Switzerland. Information on the decline in mortality before chemotherapies were introduced may be useful in developing countries where drug-resistant tuberculosis is now becoming a major problem. Swiss data were collected from historical records and comparative data were obtained from the literature for England and Wales,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Similar declines in TB mortality were also observed in other regions in the Northern hemisphere [ 1 , 3 , 4 , 6 , 21 23 , 38 , 39 ]. In all European countries, TB mortality decreased steadily, but peaked 1918 due to the influenza epidemic [ 40 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar declines in TB mortality were also observed in other regions in the Northern hemisphere [ 1 , 3 , 4 , 6 , 21 23 , 38 , 39 ]. In all European countries, TB mortality decreased steadily, but peaked 1918 due to the influenza epidemic [ 40 ].…”
Section: Discussionsupporting
confidence: 81%
“…The major decline in TB mortality took place long before effective TB drugs combination therapy became available in the 1950s, and factors other than drugs need to be considered to explain the decline [ 3 , 4 , 6 , 9 , 37 , 38 ]. Our results suggest that a combination of improvements over time, including improved housing conditions and particularly ventilation, screening for TB at schools, isolation of TB cases from the general population in TB sanatoria and open-air schools may all have contributed to the decline of TB in the city of Bern.…”
Section: Discussionmentioning
confidence: 99%
“…These included major sanitation and public health acts, notification of infectious disease requirements, compulsory reporting and development of better diagnostics (e.g. X rays), and improved nutrition [59][60][61][62][63]. For leprosy [64], it has been suggested that it is likely to have appeared during urbanisation, as there is PLOS ONE no skeletal evidence prior to this.…”
Section: Earlier Considerations Of Co-evolution Of the Diseases And Hmentioning
confidence: 99%
“…These included major sanitation and public health acts, notification of infectious disease requirements, compulsory reporting and development of better diagnostics (e.g. X rays), and improved nutrition [47][48][49][50][51]. For leprosy, [52] it has been suggested that it is likely to have appeared during urbanisation, as there is no skeletal evidence prior to this.…”
Section: Earlier Considerations Of Co-evolution Of the Diseases And Hmentioning
confidence: 99%